A case studies approach to the analysis of profiling and framing structures for pervasive information systems - Fernandes, José Eduardo (2012)
Model-Based/Driven Development (MDD) constitutes an approach to software design and development that potentially contributes to: concepts closer to domain and reduction of semantic gaps; automation and less sensitivity to technological changes; capture of expert knowledge and reuse. The widespread adoption of pervasive technologies as basis for new systems and applications, lead to the need of effectively design pervasive information systems that properly fulfil the goals they were designed for. This paper presents a profiling and framing structure approach for the development of Pervasive Information Systems (PIS). This profiling and framing structure allows the organization of the functionality that can be assigned to computational devices in a system and of the corresponding development structures and models, being. The proposed approach enables a structural approach to PIS development. The paper also presents two case studies that allowed demonstrating the applicability of the approach.